English narrative poetry : a babel of voices - Görey, Özlem (Cambridge Scholars Publishing, 2017)
Poetry, by definition, is voice, which here includes the worlds of both sound silence in which the poem exists. Voice in poetry represents the way in which individuals articulate themselves as subjects. English Narrative Poetry: A Babel of Voices explores how poets in different periods of English literature have manipulated voice in their verse narratives. This book, devoted to voice, explores narrative poems ranging from the Renaissance to the contemporary. Starting from Shakespeare, it journeys through Pope, Wordsworth, Keats, Rossetti, Browning, H.D., Ted Hughes, Jackie Kay, and Bernardine.